Costs and Benefits of Land Fragmentation : Evidence from Rwanda - Ali, Daniel Ayalew; Deininger, Klaus; Ronchi, Loraine (World Bank, Washington, DC, 2015)
This paper disentangles different aspects of land fragmentation and its impact on the efficiency of resource use. The paper uses information on the incidence of crop shocks to assess whether fragmentation provides benefits in reducing risk and parcel coordinates and terrain-adjusted travel times between parcels to more precisely account for the associated costs in 2010/11 data from Rwanda. While fragmentation increases the time required to move between a household’s parcels, this does not appear to affect overall technical efficiency on the farm. Fragmentation rather reduces the incidence of crop shocks and increases yields and productive efficiency. In Rwanda’s setting, interventions to reduce fragmentation may, therefore, be ineffective or counterproductive.